Corporate training in commercial banks: trends in the foreign financial sector - P. I. Ananchenkova; Yu. I. Donskova (Путеводитель предпринимателя, 2024)
Currently, many organizations see an urgent need for systematic and targeted development of the skills and abilities of their employees, and are reviewing their training concepts and strategies, since changes in the external and internal organizational environment require adaptation to new processes, procedures, technologies and systems. Commercial banks are no exception to this rule. International studies reflecting the practice of personnel policy and human resource management in the largest banks in the world, such as JP Morgan, Bank of America, Citigroup, KCB, Equity, Pan–African Bank, Bank of Africa, etc., show that corporate training is highly appreciated by employees, is perceived as a mechanism of motivation and employee loyalty, helps reduce turnover personnel and increase the productivity of their work. Thus, personnel development through corporate training programs becomes a necessary and integral part of the personnel policy of modern companies in the banking sector, integrated into the strategy of corporate training and personnel policy in the unity of strategic goals and objectives of general management.